Pola Komunikasi Perawat dan Pasien Rawat Inap di Rumah Sakit Haji Jakarta - Mohamad Wahyu Subakti; Noviawan Rasyid Ohorella; Edy Prihantoro; Dwi Asih Haryanti (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to determine and describe the Communication Pattern of Nurses and Patients at the Jakarta Hajj Hospital. Researchers use Communication Accommodation Theory to see the occurrence of interactive communication between nurses and patients, each individual tends to make accommodations to achieve certain goals. This study uses a qualitative approach through observation and in-depth interviews, which are then described descriptively. Based on the analysis of researchers who focused on interpersonal communication patterns showed communication between nurses and patients at Haji Hospital Jakarta. seen from the positive attitude indicators, support and equality have gone well. However, the indicators of openness and empathy have not been done well, because there are still patients who are not open to nurses and the relationship between nurses and patients is only on the outermost layer or not intimate.